Layer Influence on Organosilica Composites Strength to Withstand the Impact of 9mm Caliber Bullets - Notonegoro, Hamdan Akbar; Sofyan, Muhammad Azis; Rizkynawan, Benridho; Soegijono, Bambang; Setiawan, Jan; Aritonang, Sovian; Suherman, Andri; Ali, Nora'aini (Jurnal Sains Materi Indonesia, 2025)
The use of steel panels in conventional bulletproof vests is no longer relevant to current needs. In addition to being heavy, troop flexibility is disrupted. It is necessary to develop lighter and more reliable composite panels. The purpose of this study was to determine the ability of organosilica resin composite panels that were given variations of 5, 7 and 9 layers of woven fiberglass to withstand 9 mm caliber bullets using the NIJ-0101.06 Standard. The results of the firing test showed that the bullets were held back in the 7th and 9th layers. This result shows that this composite is a worthy candidate to replace conventional steel panels in bulletproof vests.